(3GdeMGSHI Ydi GdEfJGL hEYOGO GdbhGFe GdeGdjI aj GdTQcGJ GdbGHVI GdJGHYIs - (3hUaj YHO GdaJGM(B, (3CHh GdecGQes ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 1999)
(3GdeMGSHI Ydi GfOeGL GdTQcGJ , GdTQcGJ GdJGHYI hEYOGO GdbhGFe GdeGdjI GdehMOI YfO GdSjWQI GdcdjI Ydi TQcI JGHYI habG dCSdhH GdTQGA ,GdTQcGJ GdbGVjI hEYOGO GdbhGFe GdeGdjI GdehMOI YfO GdSjWQI GdLRFjI Ydi TQcI JGHYI habG dCSdhH GdTQGA ,GYOGO GdbhGFe GdeGdjI GdehMOI habG dCSdhH GfOeGL GdMbhb , GdbhGFe GdeGdjI GdehMOI hcjajI eYGdLI GdYedjGJ GdeJHGOdI Hjf GdbGHVI hGdJGHYIs
Keywords: (3GdTQcGJ(B-(3EfOeGLs; (3GdTQcGJ(B-(3eMGSHIs